Was kann die Stadt heute noch leisten? Integration, urbane Regimes und die Durchsetzbarkeit von Leitbildern - Peter Franz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 1997)
– Since 1990, the date of German reunification, urban development and especially the recovery of inner cities in East Germany has been delayed by several factors including real estate restitution claims, inflexible preservation codes for historic buildings, and the shortage of stores for retailers. This blockade situation has resulted in the quick and intensified development of shopping centres as 'inner city substitutes' on the urban periphery. The combined effect of the factors preventing revitalisation strategies and the newly realised and practised potential for autonomous action by the authorities of smaller municipalities was a severe restriction for the governing capacities of the authorities of the larger cities. in regaining their governance capability city governments are dependent on urban groups joining and supporting public developmental strategies. In accordance with Stone (1993) and Stoker and Mossberger (1994) urban groups active in urban development policy can be described as urban regimes. In Germany three types of regimes can be differentiated. The cities differ with respect to the political strength and the forms of coalition and conflict between different urban regimes. Specific conditions in East Germany have led to a special regime constellation with a powerful 'conservation regime' on the one hand and a vivid 'globalisation regime' on the other hand. This conflicting constellation results in a developmental blockade. The hypothesis is that a third regime type, the 'local alliance', is missing and still has to be created by practices such as city marketing and city management. Only when this regime building process has advanced will new constellations of political coalitions and compromise become possible and be able to reduce governance problems of city government in the long run.
urn:nbn:de:gbv:3:2-17894
Keywords: 330